2020
DOI: 10.3390/ijms21020669
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin Pd(T4) Exhibits Oncolytic Activity and Cumulative Effects with 5-ALA Photodynamic Treatment against C918 Cells

Abstract: Photodynamic therapy is a non-invasive method where light activates a photosensitizer bound to cancer cells, generating reactive oxygen species and resulting in cell death. This study assessed the oncolytic potential of photodynamic therapy, comparing European Medicines Agency and United States Food and Drug Administration-approved 5-aminolevulinic acid (5-ALA) to a metalloporphyrin, Pd(T4), against a highly invasive uveal melanoma cell line (C918) in two- and three-dimensional models in vitro. Epithelial mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…At a low PdT4:virus ratio (~2 µM PdT4: ~10 10 PFU/mL), a noticeable shift was observed in the PdT4 Soret peak after 5 min incubation ( Figure 1 ). This red shift is caused by porphyrin binding, most likely to bacteriophage capsid proteins, though the shift is evident with nucleic acid and lipids as well [ 18 ]. No further shift was observed between 5- and 15-min incubation periods ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a low PdT4:virus ratio (~2 µM PdT4: ~10 10 PFU/mL), a noticeable shift was observed in the PdT4 Soret peak after 5 min incubation ( Figure 1 ). This red shift is caused by porphyrin binding, most likely to bacteriophage capsid proteins, though the shift is evident with nucleic acid and lipids as well [ 18 ]. No further shift was observed between 5- and 15-min incubation periods ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Singlet oxygen acts over short distances (~150 nm) in aqueous solutions and therefore reacts with targets close to the site of formation [ 11 ]. Due to porphyrin interactions with nucleic acid, proteins, and lipids [ 18 ], viral inactivation can be mediated through disrupting multiple viral targets—i.e., envelope lipids, capsid and core proteins [ 19 ], and nucleic acids [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) action is based on the selective destruction of cancer cells or pathological vessels. The PDT mechanism uses light to activate photosensitizers, generating reactive oxygen species that kill cells [ 62 , 63 , 64 ]. Due to its specific mechanism of action, photodynamic therapy minimizes damage to normal cells [ 62 ].…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Photodynamic therapy (PDT) action is based on the selective destruction of cancer cells or pathological vessels. The PDT mechanism uses light to activate photosensitizers, generating reactive oxygen species that kill cells [53][54][55]. This reaction activates immune factors such as histamine, thromboxane, and TNF-α cytokines.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Another group of compounds commonly used in PDT is porphyrins and their derivatives. Studies carried out by Leviskas B et al have shown that Metalloporphyrin Pd (T4) is used alone or in combination with 5-aminolevulinic acid (the porphyrin synthesis precursor) is effective in PDT against highly invasive uveal melanoma cell line C918 in vitro [54].…”
Section: Photodynamic Therapymentioning
confidence: 99%